Tinjauan Hukum Ekonomi Syariah Terhadap Al-'Uqud Al-Murakkabah Dalam Praktik Jual Beli Pre Order Merch Photocard ATEEZ Pada Mangala GO - Imelda Dwi Safira; Kisanda Midisen; Yudianto Achmad; MH Ainulyaqin; Sukron Mamun (Jurnal Ilmiah Ekonomi Islam, 2026)
This study examines the pre-order (PO) buying and selling practices of ATEEZ photocard merchandise at the Mangala GO store through the lens of Islamic Economic Law, with particular emphasis on the implementation of al- ‘uqud al-murakkabah (hybrid contracts). By adopting a field research approach, this research constitutes a descriptive qualitative study. Data were obtained through a review of relevant literatures and direct observation, interview of parties actively involved in the transaction process, including sellers, personal shoppers, and buyers. The results reveal that the pre-order system applied by Mangala GO involves two types of contracts applied sequentially, namely the wakalah bil ujrah contract between the first and the second sellers as an intermediary, and the murabahah contract between the second seller and the buyer. In practice, the second seller acts as an authorized agent to order the goods and subsequently conducts a sale transaction with the buyer after the goods are obtained, with profits agreed upon transparently. According to Sharia Economic Law analysis, the implementation of this hybrid contract is considered valid and in compliance with the principles of fiqh muamalah, as it fulfills all the pillars and conditions of the contract and is free from elements of gharar, riba, and maysir. Clarity of price, cost details, product condition, and delivery time estimation are key factors ensuring the legitimacy of the transaction. This study confirms that the application of al- ‘uqud al-murakkabah in the pre-order system at Mangala GO can serve as a model for Sharia-compliant online transactions.